Analisis Tindak Tutur Lokusi pada Video Pembelajaran Cara Berpikir Kritis melalui Kanal YouTube Latih Logika - Arina Izzata Amalina; Auliana Fathiya Hanim; Lingga Dwi Andika; Moch. Yusuf Ilham Noer; Siti Rizkia Latifa; Wahidah Mustaqimah; Asep Purwo Yudi Utomo; Ermawati. S (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2025)
Locutionary speech acts are one type of speech act that focuses on a meaning contained in a sentence. This study is based on how speakers in their pronunciation do not give a little emphasis to each utterance that is uttered. The purpose of this study focuses on locutionary speech acts which describe the intent and form of locutionary speech acts in the YouTube channel Latih Logika. In the approach process in this study, using data collection methods and using the techniques of similan, libas, bebas, andcakap at the data analysis stage, using the agih and padan methods. While the data analysis presentation techniques applied in this study are formal and informal. In this study, several locutionary speech acts, question locutions, command locutions, and news locutions were produced. In 12 videos on the YouTube channel Latih Logika contains 235 speech acts of news, 49 speech acts of questions, and 50 speech acts of commands with a total data of 334. By conducting this research, the author hopes that this research can provide quite extensive benefits for readers or other researchers as a reference source and source of reference regarding locutionary speech acts.